1996
DOI: 10.1111/j.1751-1097.1996.tb02995.x
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Induced Changes in Cell Cycle and Gene Expression within Rabbit Lens Epithelial Cells

Abstract: — Damage to lens epithelial cells is a probable initiation process in cataract formation mediated by UV radiation. In these experiments, we investigated the effects of exposure to 254 nm radiation on cell cycle progression and gene expression in the rabbit lens epithelial cell line N/N1003A. The RNA was harvested at various times following exposure to UV (254 nm) radiation and analyzed by dot‐blot and northern blot hybridizations. These results revealed that during the first 6 h following exposure of the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…45,46 It has also been reported that histone transcripts accumulate with exposure of lens epithelial cells to ultraviolet C radiation. 47 The possible association of αAand αB-crystallin with histones is also consistent with their involvement in cell growth. 9,11 We further demonstrated that the absence of α-crystallins increases the amount of vimentin cross-linked with tubulin.…”
Section: ■ Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…45,46 It has also been reported that histone transcripts accumulate with exposure of lens epithelial cells to ultraviolet C radiation. 47 The possible association of αAand αB-crystallin with histones is also consistent with their involvement in cell growth. 9,11 We further demonstrated that the absence of α-crystallins increases the amount of vimentin cross-linked with tubulin.…”
Section: ■ Discussionmentioning
confidence: 57%
“…Histone H2B undergoes phosphorylation in response to apoptotic signals in mammalian cells, which may facilitate access of damaged DNA to repair mechanisms (44, 45). It has also been reported that histone transcripts accumulate with exposure of lens epithelial cells to ultraviolet C radiation (46). The possible association of αA-and αB-crystallin with histones is also consistent with their involvement in cell growth (9, 11).…”
Section: Discussionmentioning
confidence: 99%
“…␣A-crystallin has been shown to undergo phosphorylation in vivo and act as an autokinase (52). It is also noteworthy that histone transcripts accumulate in lens epithelial cells after UVC irradiation (53). The phosphorylation of heat-shock protein 60 regulates its attachment to histone H2B in the plasma membrane (54), and a nucleosome assembly protein has recently been shown to function as a histone chaperone (55).…”
Section: Figmentioning
confidence: 99%
“…Histones play a central role in the packaging of DNA into nucleosomes, comprise the basic building block of chromatin, and are involved in transcriptional regulation [ 11 13 ]; however, very little is known about the specific role of histones in the lens [ 14 , 15 ]. The expression of histone transcripts decreases in lens epithelial cells exposed to UV radiation, suggesting a response to stress [ 16 ]. Also, a recent study demonstrated that the specific acetylation of histone H3 is required for normal lens induction in the embryonic mouse eye at stage E9.5 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%